The possibilities of magnetic-resonance imaging in the evaluation of the hands in patients with juvenile idiopathic arthritis - A. K. Traudt; V. D. Zavadovskaya; L. M. Ogorodova; Z. A. Mayevskaya; Yu. P. Chasovskikh; T. V. Zhogina; A. N. Kaylina (Бюллетень сибирской медицины)
To establish the informativeness of MRI in detecting lesions in patients with intra-articular structures of juvenile idiopathic arthritis was performed MRI and radiography of hands six patients (11 hands) at the age of 10 to 17 years old (the average length of illness (42.0 ± 20.5) months)A wide range of changes in bone and soft tissue structures, including synovitis, bone erosion, tenosinovitis, bone marrow edema revealed. The advantage of MRI compared with radiography identified erosions in the amount of different localization. The proliferation of established synovitis, compared with the MRI data of clinical and laboratory parameters of inflammatory activity widespread. The data obtained from MRI can be used for diagnosis, prognosis and monitoring response to treatment, including early stage disease.